2021
DOI: 10.35699/2447-6218.2021.26590
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da modificação térmica nas propriedades físicas da madeira de Pinus caribaea var. hondurensis Barrett & Golfari

Abstract: A madeira do gênero Pinus é amplamente utilizada na indústria florestal, principalmente no setor moveleiro e civil, sendo assim, importante a busca por técnicas que melhorem e aperfeiçoem as suas propriedades tecnológicas. Neste sentido, o presente estudo teve como objetivo avaliar o efeito da modificação térmica nas propriedades físicas da madeira de Pinus caribaea var. hondurensis sob duas diferentes temperaturas. Foram utilizadas três árvores com idade de 14 anos do campo experimental da Universidade Estadu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…While conducting research with Indian teak boards, BUDHE et al [19] found that the heat treatment decreased the wood surface wettability. In research with Pinus caribaea, SANTOS and SILVA [20] observed that the process of thermal modification influenced the wood's physical properties, promoting a reduction in the equilibrium moisture, a lower hygroscopicity, and greater dimensional stability, in addition to evidencing the notoriety of the material subjected to a higher temperature. Wood constituent elements such as cellulose, hemicellulose, and lignin, during heat treatment, decompose at different temperatures and consequently have their chemical properties modified and their tendency to reduce water absorption with increasing the treatment temperature [21].…”
Section: Bulk Density and Moisture Contentmentioning
confidence: 99%
“…While conducting research with Indian teak boards, BUDHE et al [19] found that the heat treatment decreased the wood surface wettability. In research with Pinus caribaea, SANTOS and SILVA [20] observed that the process of thermal modification influenced the wood's physical properties, promoting a reduction in the equilibrium moisture, a lower hygroscopicity, and greater dimensional stability, in addition to evidencing the notoriety of the material subjected to a higher temperature. Wood constituent elements such as cellulose, hemicellulose, and lignin, during heat treatment, decompose at different temperatures and consequently have their chemical properties modified and their tendency to reduce water absorption with increasing the treatment temperature [21].…”
Section: Bulk Density and Moisture Contentmentioning
confidence: 99%